Математика 6 класс И.И.Зубарева, А.Г.Мордкович

Математика 6 класс И.И.Зубарева, А.Г.Мордкович

авторы: , .
издательство: "Мнемозина" 2014 год

Другие варианты решения
Раздел:

Номер №442

Упростите выражение:
а)
$\frac{1}{6} * (-9y)$
;
б)
$14y * (-\frac{2}{7})$
;
в)
$(-\frac{2}{5}) * (-10x)$
;
г)
$-4x * (-\frac{5}{12})$
;
д)
$3y * (-\frac{7}{15})$
;
е)
$\frac{11}{26} * (-13y)$
.

Решение а

$\frac{1}{6} * (-9y) = (-1) * \frac{1}{6} * 9y = (-1) * \frac{1}{2} * 3y = -\frac{3}{2}y = -1,5y$

Решение б

$14y * (-\frac{2}{7}) = (-1) * 14y * \frac{2}{7} = (-1) * 2y * 2 = -4y$

Решение в

$(-\frac{2}{5}) * (-10x) = \frac{2}{5} * 10 = 2 * 2 = 4$

Решение г

$-4x * (-\frac{5}{12}) = 4x * \frac{5}{12} = \frac{5}{3}x = 1\frac{2}{3}x$

Решение д

$3y * (-\frac{7}{15}) = (-1) * 3y * \frac{7}{15} = (-1) * y * \frac{7}{5} = -\frac{7}{5}y = -1,4y$

Решение е

$\frac{11}{26} * (-13y) = (-1) * \frac{11}{26} * 13y = (-1) * \frac{11}{2} * y = -5,5y$
Другие варианты решения